Techno-economic evaluation of a process for the transformation of VitAto sweet potato into value-added products - Mokhtar, Mohd Noriznan (Wiley-Blackwell, 2022)
VitAto is a popular orange sweet potato (SP) variety in Malaysia that is easy to grow, produces a large yield, and contains more nutritional components. VitAto flour is a significant ingredient in a variety of food compositions; nevertheless, establishing a cost-effective process design is critical. Five potential process scenarios were built using the SuperPro Designer simulator, with a VitAto plant capacity of 4,000 kg/h and additional income from byproducts such as VitAto juice and VitAto protein. Purchasing cost (PC), capital expenditure (CAPEX), operating expenditure (OPEX), and net present value (NPV) were used to compare the suggested projects in order to find the most efficient and profitable ones. The alternate procedure for producing VitAto juice yields a higher NPV (US$ 13,830,000–US$ 13,867,000/year). According to the data, VitAto juice is the most profitable product, accounting for 52–60% of overall project revenue. As a result, implementing a process with water recycling and byproducts revenue can be a more profitable and long-term project that will benefit Malaysia's low- and middle-income rural areas.